Concerning the Aims and Scope for JAMES. (30th April 2021) - Griffies, Stephen M.; Blyth, Eleanor; Fan, Jiwen; Pincus, Robert; Schneider, Tapio
Abstract: In this editorial, we present general principles as well as specific notions that guide the strategy of JAMES′ editors in realizing the journal's mission. Key Point: The editors of JAMES describe their strategy in realizing the journal's mission